Gemini Near Infrared Spectrograph–Distant Quasar Survey: Prescriptions for Calibrating UV-based Estimates of Supermassive Black Hole Masses in High-redshift Quasars - Dix, Cooper (2023)
The most reliable single-epoch supermassive black hole mass (MBH) estimates in quasars are obtained by using the velocity widths of low-ionization emission lines, typically the Hβ λ4861 line. Unfortunately, this line is redshifted out of the optical band at z ≈ 1, leaving MBH estimates to rely on proxy rest-frame ultraviolet (UV) emission lines, such as C IV λ1549 or Mg II λ2800, which contain intrinsic challenges when measuring, resulting in uncertain MBH estimates. In this work, we aim at correcting MBH estimates derived from the C IV and Mg II emission lines based on estimates derived from the Hβ emission line. We ﬁnd that employing the equivalent width of C IV in deriving MBH estimates based on Mg II and C IV provides values that are closest to those obtained from Hβ. We also provide prescriptions to estimate MBH values when only C IV, only Mg II, and both C IV and Mg II are measurable. We ﬁnd that utilizing both emission lines, where available, reduces the scatter of UV-based MBH estimates by ∼15% when compared to previous studies. Lastly, we discuss the potential of our prescriptions to provide more accurate and precise estimates of MBH given a much larger sample of quasars at 3.20 ≲ z ≲ 3.50, where both Mg II and Hβ can be measured in the same near-infrared spectrum.